Employment Data in Household Surveys : Taking Stock, Looking Ahead - Desiere, Sam; Costa, Valentina (World Bank, Washington, DC, 2019)
Individual-level employment data have a wide range of applications. They are used to monitor labor markets and the Sustainable Development Goals, contribute to understanding and explaining socioeconomic conditions, and may help to design and inform labor market policies. This paper is relevant for academics and policy makers who want to understand the main survey design issues behind the collection of individual-level employment data in nationally representative household surveys and the implications for data quality, particularly for women and young people. The paper reviews four survey programs (Living Standards Measurement Study, Living Standards Measurement Study–Integrated Surveys on Agriculture, Labor Force Surveys, and Demographic and Health Surveys) in 14 developing countries. First, the paper reviews the Sustainable Development Goals to identify a core set of labor market indicators and briefly discusses the International Labour Organization's definitions of key concepts that shape these indicators. Second, it assesses whether the Sustainable Development Goals labor market indicators are captured in the reviewed surveys. Third, it takes stock of current approaches to collect employment data and discusses critical survey design features, such as the structure of the labor module and the wording of the questions. Fourth, the paper examines whether these survey design features are gender and age neutral. Data from the Living Standards Measurement Study–Integrated Surveys on Agriculture are used to illustrate these issues. The paper concludes by proposing short- and medium-term objectives to improve the data quality in the Living Standards Measurement Study–Integrated Surveys on Agriculture.